Interpersonal value profiles and analysis of adolescent academic performance and social thinking - Gázquez, José J.; Sainz, Jorge; Pérez-Fuentes, María del C.; Molero, María del M.; Soler, Francisco J. (Frontiers in Psychology, 2015)
The purposes of this study were to identify interpersonal value profiles and find out whether there were any differences in academic performance and social thinking. The study sample was 885 high school students of whom 49.8% (N=441) were boys and 50.2% (N=444) were girls. The results show that students with low Benevolence and Conformity levels showed higher prevalence of failures and repeated the year more often. Furthermore, students with a high level of Recognition and Leadership and low Conformity and Benevolence are socially incompetent students. Intervention programs should to achieve high levels of kindness and consideration, respect for rules and generosity, and diminish the perception of recognition by others and exertion of authority. Thus, this study shows the values that must be worked on to improve students’ Academic Performance and social competence.